2020
DOI: 10.3390/metabo10020062
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chemometrics for Correlating Carobs Nutritional Compositional Values with Geographic Origin

Abstract: Carobs unique compositional and biological synthesis enables their characterization as functional foods. In the present study, 76 samples derived from fruit and seeds of carobs, with origin from the countries of the Mediterranean region (Cyprus, Greece, Italy, Spain, Turkey, Jordan and Palestine) were analyzed for their nutritional composition, in order to identify potential markers for their provenance and address the carobs' authenticity issue. Moisture, ash, fat, proteins, sugars (fructose, glucose, sucrose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…The strong genotype effect on K concentration is reflected in the slightly lower concentrations reported by Kokkinofta et al (2020) for carob genotypes sourced from Cyprus and Italy (9.03 and 10.33 mg g −1 dw) and the two-fold higher content (24.7 mg g −1 dw) found by Musa Özcan et al (2007) in Turkish carobs. Similarly, the genotype effect on Mg concentrations is evident not only among the genotypes currently reported, which are comparable to those found in Jordanian carobs (0.82 mg g −1 dw [ 34 ]) but, also, in comparison to Turkish genotypes that present significantly higher Mg content [ 33 ]. Calcium was the second-most abundant macro-mineral found in carob pulp in concentrations 2.21 ± 0.21 mg g −1 dw, similar to those (2.38 mg g −1 dw) reported by Kokkinofta et al (2020) but half of those reported for Turkish carobs (4.21 mg g −1 dw [ 33 ]).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The strong genotype effect on K concentration is reflected in the slightly lower concentrations reported by Kokkinofta et al (2020) for carob genotypes sourced from Cyprus and Italy (9.03 and 10.33 mg g −1 dw) and the two-fold higher content (24.7 mg g −1 dw) found by Musa Özcan et al (2007) in Turkish carobs. Similarly, the genotype effect on Mg concentrations is evident not only among the genotypes currently reported, which are comparable to those found in Jordanian carobs (0.82 mg g −1 dw [ 34 ]) but, also, in comparison to Turkish genotypes that present significantly higher Mg content [ 33 ]. Calcium was the second-most abundant macro-mineral found in carob pulp in concentrations 2.21 ± 0.21 mg g −1 dw, similar to those (2.38 mg g −1 dw) reported by Kokkinofta et al (2020) but half of those reported for Turkish carobs (4.21 mg g −1 dw [ 33 ]).…”
Section: Resultssupporting
confidence: 72%
“…The fruit moisture content stabilized at a low of 8.78–9.75% at commercial maturity (RS5 and RS6), which is similar to the levels reported by Vekiari et al (9.01% ± 0.99%; 2012) [ 17 ] and Othmen et al (9.03% ± 11.30%; 2019) [ 18 ] but higher than those of Musa Özcan et al (6.01% ± 0.11%; 2007) [ 33 ]. Moisture contents in carob pulp as high as 19.18% have been reported [ 34 ], which are likely due to premature harvest. At RS5 and RS6, the respiration rate dropped below 5 mL CO 2 kg −1 h −1 , which ranks ripe carob fruit as a very low respiring horticultural commodity, along with dates, nuts and dehydrated fruits and vegetables, predisposed for long-term storage, with a low production of vital heat [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present study also emphasizes that seasonal effect on compositional traits should also be considered. Despite previous efforts to categorize carobs according to their geographical origin ( Farag et al, 2019 ; Kokkinofta et al, 2020 ), these works suffer from the limited description either of the genetic profile or the environmental conditions where trees were grown, moreover they lack replication in time. These limitations that are not easily manageable for an underutilized tree crop like carob, warrant international cooperation for the establishment of ex situ collections of the same divergent genetic material in different agro-environmental zones to allow accurate assessment of the genotypic, agro-environmental and seasonal effects on carob compositional traits and to facilitate association mapping studies.…”
Section: Discussionmentioning
confidence: 99%
“…Kibble size was found to be an important parameter in determining the chemical characteristics of the resulting carob juice produced by different extraction methods [ 24 ]. The geographical origin, type and nutritional composition of carobs from Cyprus and other countries, were differentiated based on Fourier transform infrared (FTIR) spectroscopy and chemometrics [ 25 , 26 ]. In addition, the profile of biogenic volatile organic compounds (VOCs) emitted from carob fruit that contribute to its unique aroma, has been recently described [ 27 ].…”
Section: Introductionmentioning
confidence: 99%